Pseudo-tying injuries in a hanged person. (November 2016) - Kramer, Lena; Große Perdekamp, Markus; Geisenberger, Dorothee; Pircher, Rebecca; Pollak, Stefan; Schmidt, Ulrike
Highlights: Roping down from an elevated location with a cord wound around the wrist may produce a circular excoriation imitating an injury from tying. In hanging suicides roping down prevents an unchecked drop with potential decapitation. Due to friction, epidermal traces from the victim's skin are transferred to the rope wrapped around the wrist. Abstract: A 50-year-old man was found hanged on the concrete dam of a water reservoir. The ligature, a braided rope made of synthetic fibres, was attached to a lamp on the dam crest. The length of the rope between the fastening point and the noose was about 4 m. At autopsy, stretchmark-like intimal tears of the carotid arteries were found, but the full pattern of (internal) decapitation and severance of the cervical spine was not present. The right wrist showed two almost circular, ribbon-like abrasions initially suggesting that the man had been tied before hanging. When the ligature was examined, horny scales adhered to the noose, but were also detected away from the slip-knot. By means of a DNA analysis the epidermal traces could be assigned to the deceased. The overall picture of the findings suggested that the man had roped down from the dam crest with the ligature wrapped around his right wrist thus abrading the skin.